Analysis of Active Learning Suitability of Subjects in Information and Electronics - Kubota, Yoshikatsu; Takahashi, Akiko; Hayakawa, Yoshihiro; Kashiwaba, Yasuhiro; Yajima, Kuniaki (International Journal of Engineering Pedagogy (iJEP), 2017)
“Active Learning (AL),” the teaching method which puts emphasis on students’ active participation in class and their abilities to discover problems and solve them, has been coming under the spotlight worldwide. NIT, Sendai College, Hirose Campus is promoting AL in the field of information and electronics. Especially, we are practicing “A3 Learning System” specializing in utilizing computers. We have aggressively introduced AL in class and seen the good effects of them. However, some problems are emerging in a certain type of subjects, which may mean that there are subjects unsuitable for AL. In this paper we report large-scale analysis of introduction of AL in information and electronics field and suggest that successful introduction of AL in class depends on the type of subjects.